1986
DOI: 10.1002/j.1460-2075.1986.tb04675.x
|View full text |Cite
|
Sign up to set email alerts
|

The complete sequence and structural analysis of human apolipoprotein B-100: relationship between apoB-100 and apoB-48 forms.

Abstract: We have isolated and sequenced overlapping cDNA clones covering the entire sequence of human apolipoprotein B‐100 (apoB‐100). DNA sequence analysis and determination of the mRNA transcription initiation site by S1 nuclease mapping showed that the apoB mRNA consists of 14,112 nucleotides including the 5′ and 3′ untranslated regions which are 128 and 301 nucleotides respectively. The DNA‐derived protein sequence shows that apoB‐100 is 513,000 daltons and contains 4560 amino acids including a 24‐amino‐acid‐long s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
8

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(90 citation statements)
references
References 66 publications
2
80
0
8
Order By: Relevance
“…In our direct peptide sequencing work, we observed both V and A at residue 3849, while the amino acid deduced from our cDNA sequence 5 is A, and that deduced from the other four published DNA sequences is V. In our cDNA sequencing work, 5 we observed in some clones the same three-codon deletion in the signal peptide region (codons -1 6 to -14) as that observed by Cladaras et al, 9 and we observed both ATT (I) and CTT (L) at codon 618 (refers to the codon number in the mature peptide region) and both CCT (P) and GCT (A) at codon 892. Some of the sequence variations have also been detected as restriction fragment polymorphisms in population studies.…”
Section: Variations Among Apoproteln B-100 Sequences From Different Lsupporting
confidence: 78%
See 2 more Smart Citations
“…In our direct peptide sequencing work, we observed both V and A at residue 3849, while the amino acid deduced from our cDNA sequence 5 is A, and that deduced from the other four published DNA sequences is V. In our cDNA sequencing work, 5 we observed in some clones the same three-codon deletion in the signal peptide region (codons -1 6 to -14) as that observed by Cladaras et al, 9 and we observed both ATT (I) and CTT (L) at codon 618 (refers to the codon number in the mature peptide region) and both CCT (P) and GCT (A) at codon 892. Some of the sequence variations have also been detected as restriction fragment polymorphisms in population studies.…”
Section: Variations Among Apoproteln B-100 Sequences From Different Lsupporting
confidence: 78%
“…However, in some cases, there is circumstantial evidence that suggests sequencing errors. At codon 766, Law et al 8 observed CGA, whereas all other authors observed CAG; at codon 1391, Cladaras et al 9 observed TCT, whereas all others observed TTC; at codon 2298, Hardman et al 50 observed TAT, whereas all others observed ATT; at codon 2906, Law et al 8 observed TCG, whereas all others observed TGC; at codon 3264, Carlson et al 51 observed CTG, whereas all others observed CGT; at codon 3404, Law et al 8 observed CCG, whereas all others observed GCC; and at codon 3797, Cladaras et al 9 observed CGA, whereas all others observed CAG. In each of these cases, the differences involve the rearrangement of two or three nucleotides, a situation that is unlikely to have arisen by point mutation.…”
Section: Variations Among Apoproteln B-100 Sequences From Different Lmentioning
confidence: 93%
See 1 more Smart Citation
“…Apolipoprotein B is a complex macromolecule that exists in two primary forms in human plasma (30,31), and it is the protein determinant for the cellular recognition and uptake of LDL by the LDL receptor (32)(33)(34)(35). The binding of apolipoprotein B to the LDL receptor results in internalization and degradation of LDL, promoting the clearance of LDL from the plasma and regulating intracellular cholesterol handling and biosynthesis (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of Mutations-The R3480P mutation was caused by the substitution of cytosine for guanine at position 10,648 in complementary DNA, in exon 26 of the APOB gene on chromosome 2p24 (15,16). DNA from each of the 13,427 individuals was subjected to PCR (forward primer, 5ЈGAAAGCCTCACCTCTTACTTTTCCATTGAG3Ј, and reverse primer, 5ЈGAAATCCCATAAGCTCTTGTCATAGACCGG3Ј) with an annealing temperature of 65°C followed by digestion with MspI.…”
Section: Subjects-thementioning
confidence: 99%